Распространение и географическая изменчивость Asymblepharus alaicus (Sauria, Scincidae) - Еремченко, В.К. (Вестник зоологии, 1983)
Polytypic character of Asymblepharus alaicus (E1p at, 1901) is shown on the basis of studying geographic variability of main pholidosis characters (combination and shape of central-femple and parietal scutelli, characteristics of prefrontal, nasal and other scutelli) and on coloration peculiarities, Three subspecies (two of them being new) are described: Aa. alaicus (Elpat, 1901), A. a. yakovlevae ssp. nov and A. a. kucenkoi (Nik, 1902) comb. nov. A. a. alaicus, a nominative subspecies, differs from the two others in prefrontal scutelli with a large contact area (for most individuals), peculiar coloration and a sufficiently isolated area of distribution. A. a. yakovlevae differs from A. a. kucenkoi in peculiarities of parietal scutelli arrangement, iniegral nasal scuiellum and typical coloration.